2022
DOI: 10.1186/s12957-022-02607-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection for esophageal adenosquamous carcinoma: an analysis of 56 cases

Abstract: Background Esophageal adenosquamous carcinoma (EASC) is a rare disease. The biological behavior and treatment of this malignancy are not well studied. Methods Data from 56 patients with EASC who underwent esophagectomy were retrospectively analyzed and compared with 5028 patients with esophageal squamous cell carcinoma (ESCC). The impact of clinicopathological factors on the survival of patients with EASC was analyzed. The survival differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…When EASC was located in the upper 1/3 of the esophagus, there was no local lymph node positivity, while when located in the middle 1/3 of the esophagus, the local lymph node positivity rate reached as high as 27.70%, indicating that the middle 1/3 of the esophagus in EASC is more likely to have local lymph node metastasis, and prognosis is closely related to the local lymph node positivity rate. The main location of ASC is still controversial in the literature, with some suggesting a preference for squamous cell carcinoma characteristics in the middle part of the esophagus [31,32], while others suggest a preference for adenocarcinoma characteristics in the distal esophagus [13,25]. In our data, 60.3% of patients were located in the lower 1/3 of the esophagus, indicating a preference for adenocarcinoma characteristics.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…When EASC was located in the upper 1/3 of the esophagus, there was no local lymph node positivity, while when located in the middle 1/3 of the esophagus, the local lymph node positivity rate reached as high as 27.70%, indicating that the middle 1/3 of the esophagus in EASC is more likely to have local lymph node metastasis, and prognosis is closely related to the local lymph node positivity rate. The main location of ASC is still controversial in the literature, with some suggesting a preference for squamous cell carcinoma characteristics in the middle part of the esophagus [31,32], while others suggest a preference for adenocarcinoma characteristics in the distal esophagus [13,25]. In our data, 60.3% of patients were located in the lower 1/3 of the esophagus, indicating a preference for adenocarcinoma characteristics.…”
Section: Discussionmentioning
confidence: 47%
“…The main location of ASC is still controversial in the literature, with some suggesting a preference for squamous cell carcinoma characteristics in the middle part of the esophagus 31 , 32 , while others suggest a preference for adenocarcinoma characteristics in the distal esophagus 13 , 25 . In our data, 60.3% of patients were located in the lower 1/3 of the esophagus, indicating a preference for adenocarcinoma characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that although ADSC confuses two different tumor components, the prognosis is not a general combination of the two. Coincidentally, Yendamuri et al and Chen et al reported that the prognosis of ADSC is consistent with that of SCC [ 34 , 35 ]. In addition, Yachida et al found that ADSC had better prognosis than SCC in their series of 18 patients with this disease [ 36 ].…”
Section: Discussionmentioning
confidence: 94%
“…Regarding chemotherapy for advanced ASC, Chen argued that the prognosis was similar to that of esophageal squamous cell carcinoma [ 7 ]. Evans et al .…”
Section: Discussionmentioning
confidence: 99%